Human insulin B24 (Phe----Ser). Secretion and metabolic clearance of the abnormal insulin in man and in a dog model. - Shoelson, S E (1984)
We have already demonstrated that a hyperinsulinemic, diabetic subject secreted an abnormal insulin in which serine replaced phenylalanine B24 (Shoelson S., M. Fickova, M. Haneda, A. Nahum, G. Musso, E. T. Kaiser, A. H. Rubenstein, and H. Tager. 1983. Proc. Natl. Acad. Sci. USA. 80:7390-7394). High performance liquid chromatography analysis now shows that the circulating insulin in several other family members also consists of a mixture of the abnormal human insulin B24 (Phe----Ser) and normal human insulin in a ratio of approximately 9.5:1 during fasting. Although all affected subjects show fasting hyperinsulinemia, only the propositus and her father are overtly diabetic. Analysis of the serum insulin from two nondiabetic siblings revealed that normal insulin increased from approximately 2 to 15% of total serum insulin after the ingestion of glucose and that the proportion of the normal hormone plateaued or fell while the level of total insulin continued to rise. Animal studies involving the graded intraportal infusion of equimolar amounts of semisynthetic human [SerB24]-insulin and normal human insulin in pancreatectomized dogs (to simulate the secretion of insulin due to oral glucose in man) also showed both a rise in the fraction of normal insulin that reached the periphery and the attainment of a brief steady state in this fraction while total insulin levels continued to rise. Separate experiments documented a decreased hepatic extraction, a decreased metabolic clearance rate, and an increased plasma half-life of human [SerB24]-insulin within the same parameters as those determined for normal human insulin. These results form a basis for considering (a) the differential clearance of low activity abnormal insulins and normal insulin from the circulation in vivo, and (b) the causes of hyperinsulinemia in both diabetic and nondiabetic individuals who secrete abnormal human insulins.